Immunotherapy response and resistance in patients with advanced uveal melanoma: a retrospective cohort study - Maurer, Alexander; Clerici, Giulio; Schaab, Jan A.; Cheng, Phil F.; Mihic-Probst, Daniela; Mader, Cäcilia; Messerli, Michael; Huellner, Martin W.; Dummer, Reinhard; Dimitriou, Florentia (Clinical and experimental medicine, 2024)
Metastatic uveal melanoma (mUM) is associated with poor prognosis. Ipilimumab/nivolumab has shown antitumor efficacy in phase II studies. Tebentafusp resulted in longer overall survival (OS) compared to investigator`s choice in a phase III study. We sought to describe the radiological response patterns of mUM patients treated with immunotherapy. Patients with mUM treated with ipilimumab/nivolumab and tebentafusp between July 2018 and December 2022, with available radiological assessment per RECISTv1.1 and/or imPERCIST5, were retrospectively identified and included. Progression-free survival (PFS) and OS rates, liver-specific response and pathological assessment in available liver biopsies were evaluated. In the ipilimumab/nivolumab group, median PFS (mPFS) was 2.9 months (95% CI 2.2–28.6) and mOS 28.9 months (95% CI 12.7-NR). Complete (CMR) and partial (PMR) metabolic response per imPERCIST5, and partial response (PR) per RECISTv1.1 were associated with longer PFS and OS by trend, compared to morphologically and metabolically stable or progressive disease. In the tebentafusp group, mPFS was 2.7 months (95% CI 2.2–3) and mOS 18.6 months (95% CI 11.5-NR). PMR and PR were associated with longer PFS by trend. In both treatments, the overall treatment response was associated with the radiological response at the liver site. In available liver tumor biopsies, differences in pathological and radiological responses were noted. ImPERCIST5 and RECIST v1.1 are valuable tools in the radiological response assessment, but both methods display limitations. Accurate biomarkers to stratify patients at risk for disease progression and future translational studies to investigate mechanisms of response and resistance are required.